Science Learning Based on the Guided Inquiry Model: An Effort to Improve the Science Concept Understanding of Students - Armi Larasati; Lud Waluyo; Beti Istanti Suwandayani (Postgraduate, University of Mataram, 2025)
This study aims to analyse the effect of the guided inquiry learning model on the understanding of science concepts among seventh-grade students regarding motion and force material according to the Merdeka Curriculum. The research used a quasi-experimental method with a non-equivalent control group pretest-posttest design. The sample consisted of 56 seventh-grade students from SMPN 2 Narmada, selected using cluster random sampling technique, with class VII A serving as the control group and VII B as the experimental group. The research results show that the average post-test score of the experimental class (70.54) is higher than that of the control class (51.43), and there is a significant difference based on the independent t-test (p < 0.05) using the IBM SPSS 23 application. The improvement in students' conceptual understanding is indicated by an N-Gain value of 0.5078, which falls into the moderate category. This confirms that the guided inquiry learning model has a positive effect on students' understanding of science concepts